2013
DOI: 10.1590/0074-0276130369
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale patterns in morphological diversity and species assemblages in Neotropical Triatominae (Heteroptera: Reduviidae)

Abstract: We analysed the spatial variation in morphological diversity (MDiv) and species richness (SR) for 91 species of Neotropical Triatominae to determine the ecological relationships between SR and MDiv and to explore the roles that climate, productivity, environmental heterogeneity and the presence of biomes and rivers may play in the structuring of species assemblages. For each 110 km x 110 km-cell on a grid map of America, we determined the number of species (SR) and estimated the mean Gower index (MDiv) based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 75 publications
(101 reference statements)
2
15
0
1
Order By: Relevance
“…Thus, SEVM is a popular spatial model in applied studies (Pace et al., ). Indeed, many studies also suggested that SEVM can achieve the aim of accounting for spatial autocorrelation in ecological data (Fergnani, Ruggiero, Ceccarelli, Menu, & Rabinovich, ; Gouveia, Hortal, Cassemiro, Rangel, & Diniz‐Filho, ; McClain, Allen, Tittensor, & Rex, ; Murakami & Griffith, ; Yang et al., ). A truncation distance of 215.9 km for males and 316.9 km for females, calculated in SAM (Spatial Analysis in Macroecology), version 4.0 (Rangel, Diniz‐Filho, & Bini, ), was used to create the spatial filters.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, SEVM is a popular spatial model in applied studies (Pace et al., ). Indeed, many studies also suggested that SEVM can achieve the aim of accounting for spatial autocorrelation in ecological data (Fergnani, Ruggiero, Ceccarelli, Menu, & Rabinovich, ; Gouveia, Hortal, Cassemiro, Rangel, & Diniz‐Filho, ; McClain, Allen, Tittensor, & Rex, ; Murakami & Griffith, ; Yang et al., ). A truncation distance of 215.9 km for males and 316.9 km for females, calculated in SAM (Spatial Analysis in Macroecology), version 4.0 (Rangel, Diniz‐Filho, & Bini, ), was used to create the spatial filters.…”
Section: Methodsmentioning
confidence: 99%
“…2), which also correspond to areas with the greatest diversity of species of triatomines. In the past, some of these vectors had secondary importance in the cutaneous transmission, but now they have great relevance in the oral transmission (Fergnani et al, 2013). The map of Figure 2 summarizes the most important vectors of each eco-region, as well as reservoirs, potential sources of infection and the DTUs, isolated from each outbreak of oral transmitted ChD.…”
Section: The Risk Of Chd Infection In Panama and In The Brazilian Amamentioning
confidence: 99%
“…The group has been employed in macroecological studies in attempts to understand its richness and distribution patterns on the Neotropics (e.g., Rodriguero and Gorla 2004 ;Diniz-Filho et al 2013 ;Fergnani et al 2013 ). Rodriguero and Gorla ( 2004 ) examined how New World Triatominae species richness responds to latitudinal gradients and explored the relevance of geographical area and available energy.…”
Section: Distributional Patterns Of Neotropical Heteropteramentioning
confidence: 99%
“…The unique effects of these variables are quite diffi cult to disentangle because of the collinearity among variables and residual autocorrelation and may also be due to low taxonomic sampling. Fergnani et al ( 2013 ) conducted a complementary study to understand largescale spatial patterns of morphological diversity and species richness of triatomine species in terms of environmental gradients. Studying 91 species and 12 morphological attributes of Neotropical triatomine, they found the latitudinal gradient of species richness to be in agreement with previous studies (Rodriguero and Gorla 2004 ;Diniz-Filho et al 2013 ).…”
Section: Distributional Patterns Of Neotropical Heteropteramentioning
confidence: 99%
See 1 more Smart Citation